Frank Layman (left to right), Bert Crary, Walter Boyd, Hugh Bennett, and Ed Robinson celebrate Christmas inside a sno-cat - Cromie, William J. (Byrd Polar Research Center, The Ohio State University, 1957)
Credit: William J. Cromie